Performance analysis of a biomass powered micro-cogeneration system based on gasification and syngas conversion in a reciprocating engine. (1st November 2018) - La Villetta, M.; Costa, M.; Cirillo, D.; Massarotti, N.; Vanoli, L.
Highlights: A review of micro combined heat and power bioenergy systems is presented. Features of an innovative bioenergy system (20kWe and 40kWth ) are shown. An experimental characterization of the bioenergy system is realized. Global energy balance and Sankey diagram are presented. The effects of users' temperature on efficiencies of the bioenergy system are shown. Abstract: The present paper describes an experimental characterisation of a biomass powered micro-cogeneration system based on the coupling between a gasifier and an internal combustion engine. The ECO 20 unit is sized to deliver a maximum electrical and thermal power of 20 kWe and 40 kWth, respectively. In order to highlight possible inefficiencies along the biomass-to-energy conversion chain, the global energy balance of the system under real working conditions is derived. Ultimate and proximate analyses of the processed biomass are performed, accompanied by temperature and mass flow rate measurements and gas chromatograph characterization of collected samples of the produced syngas. The greatest inefficiency is found in the gasification section with a value of the cold gas efficiency in the range of 57–60%. The low quality of the syngas (lower heating value equal to 3731 kJ/Nm 3 ) affects the engine combustion efficiency, hence its electrical efficiency that does not exceed 22.5%. The global electrical efficiency of the plant is equal to about 13.5%. As a further analysis, waste heat recovery is considered under different conditions by decreasing the temperature of the water flowing in the secondary circuit from 68.35 °C to 20.50 °C for the use of the provided thermal energy. This determines an increase of the thermal efficiency of the engine from 11.3% to 56.2%, while the global thermal efficiency increases from 6.46% to 33.72%. A feature of the ECO 20 system is the cooling of the syngas delivered to the engine by its same cooling water, for a considerable advantage on volumetric efficiency with respect to other analogous systems, also in the cases the thermal power is not utilised.